Natural and technogenic components of megalopolis magnetic field - Orlyuk, M.; Romenets, A.; Orliuk, I. (Geofizicheskiy Zhurnal, 2016)
Magnetic storm influence becomes more and more interesting for people. In this article we describe measurable magnetic field data from different megalopolis regions and from the underground passenger transport on the Kyiv city example. There were five observation points evenly situated among the city, and one metro route with direct and reverse direction movement. Collected information shows general situation with magnetic noise in populous cities. Smartphones are very popular today so we have used one of them as a budget magnetometer in our research.